Development and Validation of Contextualized Video Lessons as Home-based Intervention in Physics for Grade 9 Students - Borabo, Jonnell; Ricafort, Jhonner D. (IJOEM Indonesian Journal of E-learning and Multimedia, 2025)
Background of Study: In the 21st century teaching and learning, technology plays a vital role in improving students’ performance. In Physics learning where developing critical thinking and problem-solving skills was a challenge, technology integration like video-based instruction could be of huge impact.Aims and scope of the paper: This study aimed to develop and validate contextualized video lessons as a home-based intervention in physics for grade 9 students.Methods: The research used the developmental research design using the ADDIE model and pre-experimental research using the pretest-posttest design. Six validators consisting of physics and physical science teachers and thirty grade 9 low-performing students were selected using purposive sampling. The validity of the contextualized video lessons was assessed by the validators in terms of content, instructional and technical quality. Furthermore, the effectiveness of the contextualized video lessons as home-based intervention was determined using the students’ pretest and posttest results.Results: The video lessons were contextualized by embedding simulations, animations, diagrams and problem-solving of real-life applications of the physics concepts. The results revealed that the contextualized video lessons passed all the criteria with a very satisfactory rating. Moreover, the contextualized video lessons were effective as a home-based intervention in physics, as shown in the significant increase between the pretest and posttest scores (p < .001) with an effect size of Cohen’s d = 3.29.Conclusion: The contextualized video lessons as a home-based intervention significantly improve the performance of grade 9 students in Physics.